Light Availability and Patterns of Allocation to Reproductive and Vegetative Biomass in the Sexes of the Dioecious Macrophyte Vallisneria spinulosa - Li, Lei; Ding, Mingming; Lan, Zhichun; Zhao, Yao; Chen, Jiakuan (Frontiers in Plant Science, 2019)
Environmental changes, e.g. eutrophication, in aquatic ecosystems can greatly alter light available to submerged macrophytes. In dioecious plants, given potential for sex-specific differences in resource requirements (i.e., high-carbon for seeds vs. high-nitrogen for pollen), females and males are expected to divergently adjust allocations towards resource acquisition structures when resources are limited during growth. Here, Vallisneria spinulosa was used as a representative dioecious submerged macrophyte to detect sex-specific responses to light limitation and assess whether sexual dimorphism varied with resource availability. Plants were grown under varying levels of light availability in nine outdoor mesocosms for 14 weeks. Late in the reproductive season, allocations to vegetative and reproductive traits for both sexes were determined and relative allocations to reproduction vs. vegetative growth was analyzed. Female and male reproductive plants differed in adjustments of resource allocation in response to light availability. Under low light, females showed a smaller reduction in allocation of resources to vegetative tissues and greater leaf area than males, suggesting female plasticity to increase carbon capture. Under low light, males showed a smaller reduction in reproductive allocation than females (flowers and inflorescences in males vs. fruits in females), suggesting that carbon limitation has greater impacts on sexual reproduction by females than males. Our study provided evidence of differences in reproductive costs and currencies for female vs. male reproduction in aquatic macrophytes, as V. spinulosa responded plastically to reduced light, with sexually dimporphic allocation strategies. Sex-related resource currencies are potentially important drivers for sex-specific variations in allocation patterns, with females safeguarding their vegetative carbon-rich biomass to satisfy future fruit and seed production.